Musical Heritage and Cultural Identity: Interpreting the Symbolic Meaning of Silotuang in Dayak Bidayuh Life - Ramadhan, Iwan; Sagala, Mastri Dihita; Putra, Zakarias Aria Widyatama; Olendo, Yudhistira Oscar; Dewantara, Jagad Aditya; Hardiansyah, Muhammad Agus (Universitas Andalas, 2025)
This study aims to preserve and maintain the traditions and local wisdom values of the Dayak Bidayuh community in Jagoi Village through investigations conducted to enhance understanding of Indonesia's rich cultural diversity. This research addresses the lack of appreciation for the traditional musical instrument Silotuang, especially among the younger generation. In the face of rapid globalization, many traditions are at risk of extinction, making it crucial to document and analyze the values in the